Based on Temporal and Spatial Traffic Characteristics for Energy-Efficient Wi-Fi Network. (23rd October 2021) - Li, Zhigang; Wang, Xin; Yue, Xinan; Zou, Dongyao; Li, Jun; Si, Lina
Abstract : With the rapid development of information and communication technology (ICT) industry, the energy consumption caused by the development of mobile communications is increasing exponentially. Huge energy consumption and increasing environmental awareness prompt people to study the dynamic distribution of users and traffic in Wi-Fi networks in order to design an energy-efficient mechanism for Wi-Fi networks. Based on real data, this paper explores the spatial and temporal characteristics of human mobility and data traffic distribution. The results of access point (AP) traffic analysis show a tidal effect and obvious periodicity in time and space dimension, which can be used for the dynamic design of AP sleep or shutdown strategy. At the same time, we design a new service area (SA) zooming and AP cooperation mode. Through the simulation experiment, we find that the energy consumption can be reduced by about 35% and the communication service quality can be guaranteed.